Switchable All‐Dielectric Metasurfaces for Full‐Color Reflective Display. Issue 8 (18th February 2019) - Liu, He; Yang, Hao; Li, Yuanrui; Song, Boxiang; Wang, Yifei; Liu, Zerui; Peng, Liang; Lim, Haneol; Yoon, Jongseung; Wu, Wei
Abstract: High energy consumption and lack of readability under bright sunlight of conventional transmissive display technology greatly limit the user experience of mobile and wearable devices. To solve this issue, a hybrid display by overlaying a full‐color reflective display on top of a transmissive display is invented. The key component of this technology is a full‐color reflective display based on tandem switchable all‐dielectric metasurfaces. The switchable all‐dielectric metasurfaces in large size (average area ≈5 cm 2 ) are invented and fabricated by low‐cost and high‐throughput nanoimprint lithography. Each switchable metasurface is formed by an array of TiO2 /SiO2 hybrid nanopillars on top of a SiO2 substrate, which could reflect a unique color (blue, green, or red) light with high efficiency (bandwidth ≈100 nm and reflectance ≈80%). They become highly transparent (switched‐off) upon high‐index liquid injection. These metasurfaces demonstrate great characteristics such as polarization independence, large viewing angle (up to 60°), and ultra‐high resolution (over 6000 pixels per inch). This kind of full‐color reflective display can be combined with traditional transmissive display to achieve a low‐power hybrid display that performs well from totally dark to bright sunlight conditions. That resolves one of the biggest challenges in mobile and wearable device industry. Abstract : A full‐color reflective display based on tandem switchable all‐dielectric metasurfaces is demonstrated. Each metasurface is switchable by injecting high‐index liquid and demonstrates great characteristics such as polarization independence, large viewing angle and ultra‐high resolution. The full‐color reflective display can be combined with transmissive display to achieve a low‐power hybrid display and performs well from dark to bright sunlight lighting conditions.